HUBUNGAN BIG FIVE PERSONALITY TERHADAP STRES BELAJAR SISWA DI SMP NEGERI 4 TARAKAN - Oktavia, Nur Lina; Rahmi, Siti; Suriata, Suriata (Universitas Borneo Tarakan, 2023)
AbstractThe research objective was to determine the relationship between the big five personality and learning stress in studends at SMP Negeri 4 Tarakan. The research method use is quantitative research with correlation approach. Human personality can be seen from the five dimentions of the big five personality; openness to experiences, conscientiousness, extraversion, agreeableness, and neuroticism, which have various relationship to learning stress. The study found that the velue of the extraversion personality dimention had a correlation value of 0.107. it indicate a very low relationship between extraversion and learning stress. As for agreeableness, the correlation value -144 describe a negative relationship between agreeableness and learning stress. The conscientiousness value 0.136 defines a very low relationship between conscientiousness and learning stress. Then neuroticism has a correlation value of -161, meaning a negative relationship exists between neuroticism and learning stress. The correlation test analysis’s openness to experience value is 0.167, meaning a very low relationship exists between openness to experience and learning stress. It describes a positve relationship between extraversion, conscientiousness, and openness to experience personality dimentions will be the higher the learning stress. Conversely, the lower the personality dimentions of extraversion, conscientiousness, and openness to experience, the lower the learning stress for student will be. On personality dimentions, agreeableness and neuroticism have a negative relationship with learning stress. It means that the higher the agreeableness and neuroticism, the lower the student’s learning stress. Conversely, the lower the agreeableness and neuroticism, the higher the learning stress in students. Keywords: Big Five Personality, Learning Stress AbstrakTujuan penelitian yaitu untuk mengetahui adanya hubungan big five personality dengan stres belajar pada siswa di SMP Negeri 4 Tarakan. Metode penelitian yang digunakan adalah penelitian kuantitatif dengan pendekatan korelasi. Kepribadian manusia dapat dilihat dari lima dimensi kepribadian big five personality yaitu, oppenness to experiences, conscientiousness, extraversion, agreeableness, and neuroticims yang mempunyai hubungan bervariasi pada stres belajar. Hasil penelitian didapati nilai dimensi kepribadian extraversion nilai korelasi sebesar 0,107 dapat disimpulkan bahwa terdapat hubungan yang sangat rendah antara extraversion dengan stres belajar. Adapun agreeableness nilai korelasi -144 maka dapat disimpulkan bahwa adda hubungan negatif antara agreeableness dengan stres belajar lalu nilai conscientiousness analisa uji korelasi sebesar 0,136 artinya terdapat hubungan yang sangat rendah cientiousness dengan stres belajar selanjutnya neuroticism nilai korelasi -161 dapat disimpulkan bahwa terdapat hubungan negatif antara neuroticism dengan stres belajar. Dan nilai openness to experience analisa uji korelasi sebesar 0,167 artinya terdapat hubungan yang sangat rendah antara openness to experience dengan stres belajar. Maka dapat disimpulkan bahwa hubungan antara adanya hubungan yang positif antara dimensi kepribadian extraversion, conscietiousness, dan openness to experience maka stress belajar akan semakin tinggi. Sebaliknya semakin rendah dimensi kepribadian extraversion, conscietiousness, dan openness to experience maka stress belajar pada siswa akan semakin rendah pula. Pada dimensi kepribadian agreeableness dan neuroticism memiliki hubungan negatif dengan stres belajar. Artinya semakin tinggi agreeableness dan neuricism maka semakin rendah stres belajar siswa. Sebaliknya semakin rendah agreeableness dan neuroticism maka semakin tinggi pula stres belajar pada siswa. Kata kunci: Big Five Personality, Stres Belajar